PENGARUH DIGITAL MARKETING, INOVASI, DAN KUALITAS FORE COFFEE TERHADAP KEPUTUSAN PEMBELIAN DI CABANG MEGA MALL KOTA BATAM - Andrew Andrew; Asron Saputra (SCIENTIA JOURNAL, 2025)
This study aims to determine the influence of Digital Marketing, innovation, and the quality of Fore Coffee on purchasing decisions at the Mega Mall Batam branch, both partially and simultaneously. The sample consisted of 384 respondents selected using purposive sampling. Data were collected through an online questionnaire distributed via Google Forms. Data analysis was conducted using SPSS version 30, involving tests such as data quality testing, classical assumption testing, influence testing, and hypothesis testing. The results indicate that Digital Marketing, innovation, and the quality of Fore Coffee have a positive and significant effect on purchasing decisions, both partially and simultaneously.